A pilot trial of emergency telemedicine in regional Western Australia. (October 2013) - Herrington, Garth; Zardins, Yvonne; Hamilton, Alan
An Emergency Telehealth Service (ETS) was established in August 2012 in Western Australia. High definition videoconferencing was used to deliver emergency telemedicine to rural emergency departments, mainly staffed by nurses. In the first 11 months, over 3000 episodes of care were provided. Telemedicine proved useful for many clinical problems and allowed clinicians to diagnose, treat and manage patients locally, reducing the need for transfer. In addition, ETS physicians assisted with clinical coordination and transfer of patients. Almost all teleconsultations (98%) were with nursing staff at sites without medical cover. Expansion of the ETS throughout Western Australia is currently being planned.